Qualitative content analysis of “Hello Songs” composed for children by music therapists in the Czech Republic and USA - Kantor, Jiří; Kružíková, Lenka (Social Welfare: Interdisciplinary Approach, 2016)
“Hello Songs” is a ritual musical expression of the non-musical communication occurring at the beginning and the end of a music therapy session with a client. 49 “Hello Songs” composed for children by 11 Czech and 8 American music therapists were examined during a qualitative research described in this paper. Through inductive content analysis seven categories were identified that characterise the content of the “Hello Songs”, and four findings described that relate to good practice in composition and application of the songs. Recommendations for music therapy practice were formulated based on the results.